Ojibwa family. / J. Borry - Borry, Jacob, -1936, photographer. (William L. Clements Library, 1890)
Studio group portrait of unidentified Ojibwa Indian family posing before illustrated backdrop including two men, one woman and two children. The men wear mixtures of western and traditional clothing including broad brimmed hats, otter fur hair wraps, bead embroidered bandolier bags, and leggings. Man at left holds rifle while the other holds handgun. The woman and children wear western clothing.; Title devised by cataloger.; "Ojibwa Indians" variant names: Anishinaabe, Chippewa Indians, Ojibwe Indians.